Cholesterol modulates the interaction of the islet amyloid polypeptide with membranes. (November 2014) - Caillon, Lucie; Duma, Luminita; Lequin, Olivier; Khemtemourian, Lucie
Abstract The deposition of insoluble amyloid fibrils resulting from the aggregation of the human islet amyloid polypeptide (hIAPP) within the islet of Langerhans is a pathological feature of type 2 diabetes mellitus (T2DM). Increasing evidence indicates that biological membranes play a key role in amyloid aggregation, modulating among others the kinetics of amyloid formation, and being the target of toxic species generated during amyloid formation. In T2DM patients, elevated levels of cholesterol, an important determinant of the physical state of biological membranes, are observed in β-cells and are thought to directly impair β-cell function and insulin secretion. However, it is not known whether cholesterol enhances membrane-interaction or membrane-insertion of hIAPP. In this study, we investigated the effect of cholesterol incorporated in zwitterionic and anionic membranes. Our circular dichroism and liquid state NMR data reveal that 10–30% of cholesterol slightly affects the aggregational and conformational behaviour of hIAPP. Additional fluorescence results indicate that 10 and 20% of cholesterol slightly slow down the kinetics of oligomer and fibril formation while anionic lipids accelerate this kinetics. This behavior might be caused by differences in membrane insertion and therefore in membrane binding of hIAPP. The membrane binding affinity was evaluated using 1H NMR experiments and our results show that the affinity of hIAPP for membranes containing cholesterol is significantly smaller than that for membranes containing anionic lipids. Furthermore, we found that hIAPP-induced membrane damage is synchronized to fibril formation in the absence and in the presence of cholesterol.